Biotechnological Approaches for Sandalwood (Santalum album L.) Micropropagation - Bapat, V. A.; Rao, P. S. (Indian Forester, 1992)
Advancements in Biotechnological research has opened up new avenues for rapid multiplication of forest trees. The paper presented here on micropropagation of sandalwood has described various experiments conducted during the last decade in our laboratory. The tree sandalwood has proved to be a very versatile material for tissue culture research. Success has been achieved in regenerating plantiets from somatic embryos differentiated from callus tissues originating from hypocotyl, stem and protoplasts cultures. Plantlets could be regenerating from synthetic seeds prepared by encapsulating somatic embryos in a proper matrix. Viable plantlets were recovered from somatic embryos grown in a bioreactor.